The high content of β-carotene present in orange-pulp fruits of Carica papaya L. is not correlated with a high expression of the CpLCY-β2 gene. (October 2017) - Chan-León, Arianna C.; Estrella-Maldonado, Humberto; Dubé, Pascal; Fuentes Ortiz, Gabriela; Espadas-Gil, Francisco; Talavera May, Carlos; Ramírez Prado, Jorge; Desjardins, Yves; Santamaría, Jorge M.
Abstract: We investigated the transcriptional regulation of six genes involved in carotenoid biosynthesis, together with the carotenoid accumulation during postharvest ripening of three different papaya genotypes of contrasting pulp color. Red-pulp genotype (RPG) showed the lowest content of yellow pigments (YP), such as β-cryptoxanthin, zeaxanthin, and violaxanthin, together with the lowest relative expression levels (REL) of CpLCY-β2 and CpCHX-β genes. On the contrary, the yellow-pulp genotype (YPG) showed the highest content of YP and the highest REL of CpLCY-β2 and CpCHX-β genes. Interestingly, the orange-pulp genotype (OPG) showed intermediate content of YP and intermediate REL of CpLCY-β2 and CpCHX-β genes. The highest content of β-carotene shown by OPG despite having an intermediate REL of the CpLCY-β2 genes, suggests a post-transcriptional regulation. Thus, the transcriptional level of the genes, directing the carotenoid biosynthesis pathway, can partially explain the accumulation of carotenoids during the postharvest ripening in C. papaya genotypes of contrasting pulp color. Graphical abstract: Highlights: Red fruits had the highest content of lycopene and the highest REL of CpZDS gene. Yellow fruits had highest content of YP and the highest REL of CpLCY-β2 and CpCHX-β genes. Orange fruits had highest content of β-carotene despite having intermediate REL of CpLCY-β2 gene. No correlation between CpLCY-β2 REL and β-carotene suggests post-transcriptional regulation.